2012
DOI: 10.1364/ol.37.003195
|View full text |Cite
|
Sign up to set email alerts
|

A 116-μm-radius disk cavity in a sunflower-type circular photonic crystal with ultrahigh quality factor

Abstract: We present a 1.16-µm-radius disk cavity with ultrahigh quality (Q) factor by embedding the disk into a sunflower-type circular photonic crystal (CPC). The band gap of the CPC reduces the bending loss of the whispering-gallery mode of the disk, leading to a simulated Q of 10 7 , at least one order of magnitude higher than a bare disk of the same size. The design is experimentally verified with a record high loaded Q of 7.4 × 10 5 measured from an optimized device fabricated on a silicon-on-insulator substrate.O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Due to the small device size, the disk cavities exhibit a single resonance peak over a wavelength range of tens of nanometers118. Figure 2 shows the zoomed optical transmission spectra of an undercoupled device (Device 1) measured under three different conditions: (a) in air at room temperature (298 K), (b) immersed in superfluid helium near the lambda point (at 2.168 K), and (c) far below the lambda point (at 2.000 K).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the small device size, the disk cavities exhibit a single resonance peak over a wavelength range of tens of nanometers118. Figure 2 shows the zoomed optical transmission spectra of an undercoupled device (Device 1) measured under three different conditions: (a) in air at room temperature (298 K), (b) immersed in superfluid helium near the lambda point (at 2.168 K), and (c) far below the lambda point (at 2.000 K).…”
Section: Resultsmentioning
confidence: 99%
“…With the bandgap effect, the photonic crystal structure provides excellent confinement to the disk's whispering-gallery modes and leads to their ultrahigh Q factors beyond that of bending-loss limit. Structure optimization is performed with MEEP by a three-dimensional FDTD method27, where the disk radius, the photonic crystal's lattice constant and hole radius, and the gap between the disk and the photonic crystal are all optimized in a multi-variable parameter space to maximize the cavity Q factor18.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency band with 20 dB lower transmission efficiency than the passband, can be regarded as a PBG [16,48], so the frequency band lower than −20 dB transmission efficiency is generally considered as a PBG in this paper. As shown in figure 2, it is found that DC magnetic field changes the PBGs of CPC with YIG rods and increases the number of peak points, which is because the off-diagonal elements in permeability tensor induced by the nonzero bias magnetic field break the time-reversal symmetry of PC and the damage degree of breakage is characterized by the ratio of κ to µ.…”
Section: Model and Theorymentioning
confidence: 99%
“…CPC, should be adopted in order to facilitate the practical preparation, reduce the bending loss and generate one-way rotating state that has as many frequency bands as possible. In addition, CPC can generate isotropic PBG characteristic [42] and can be extensively applied in fiber [5,6], sensor [16], curved waveguides [43][44][45], directional coupler [46,47], and resonant cavity [48], for the possession of the ultra-flat dispersion, high sensing sensitivity, low bending loss and high quality factor.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this issue, centrosymmetric mechanical resonators, such as wheel 82,83 and disk resonators 84,85 can be employed, which have the advantage that they can be easily designed to host mechanical resonances and optical resonances simultaneously. In this case the entire optical resonator is made free-standing, thus avoiding degradation of the optical resonator performance.…”
Section: Diamond Nanomechanical Resonatorsmentioning
confidence: 99%